Dynamic imaging of a single gold nanoparticle in liquid irradiated by off-resonance femtosecond laser. Issue 27 (24th June 2015) - Boutopoulos, Christos; Hatef, Ali; Fortin-Deschênes, Matthieu; Meunier, Michel
Abstract : Direct imaging of a single gold nanoparticle acting as durable nanolens under off-resonance femtosecond laser irradiation. Abstract : Plasmonic nanoparticles can lead to extreme confinement of the light in the near field. This unique ability of plasmonic nanoparticles can be used to generate nanobubbles in liquid. In this work, we demonstrate with single-particle monitoring that 100 nm gold nanoparticles (AuNPs) irradiated by off-resonance femtosecond (fs) laser in the tissue therapeutic optical window ( λ = 800 nm), can act as a durable nanolenses in liquid and provoke nanocavitation while remaining intact. We have employed combined ultrafast shadowgraphic imaging, in situ dark field imaging and dynamic tracking of AuNP Brownian motion to ensure the study of individual AuNPs/nanolenses under multiple fs laser pulses. We demonstrate that 100 nm AuNPs can generate multiple, highly confined (radius down to 550 nm) and transient (life time < 50 ns) nanobubbles. The latter is of significant importance for future development of in vivo AuNP-assisted laser nanosurgery and theranostic applications, where AuNP fragmentation should be avoided to prevent side effects, such as cytotoxicity and immune system's response. The experimental results have been correlated with theoretical modeling to provide an insight to the AuNP-safe cavitation mechanism as well as to investigate the deformation mechanism of the AuNPs at high laser fluences.